Differential Drawdown of Ammonium, Nitrate, and Urea by Freshwater Chlorophytes and Cyanobacteria1. Issue 2 (18th January 2020) - Erratt, Kevin J.; Creed, Irena F.; Trick, Charles G.
Abstract : The chemical form of nitrogen (N) is deemed to be decisive in shaping the composition of the primary producer community. Recently, there has been a shift in the dominant form of N delivered to agricultural landscapes. Urea‐based fertilizers are a mainstay in modern agriculture, and their ubiquitous use has increased the likelihood of urea export to nearby freshwaters. The shift to urea fertilizers has coincided with the recent expansion of cyanobacteria harmful algal blooms (cyanoHABs). This study investigated N drawdown patterns between two major freshwater phytoplankton groups—chlorophytes and cyanobacteria. Experiments were designed to understand if different patterns of N drawdown occurred among taxa and the potential synergistic effects of multiple N substrates. Nitrate (NO3 − ), ammonium (NH4 + ), and urea were supplied in a series of paired combinations, and N concentrations were monitored to track N drawdowns. We did not find significant differences between phytoplankton classes when supplied with a single N substrate. However, we found that when N substrates were supplied in combination, significant differences in N drawdown patterns were observed. Urea was consumed more rapidly among cyanobacteria, being drawn down at significantly higher rates relative to inorganic N substrates. In contrast, inorganic N substrates were drawn down more rapidly among chlorophytes relative to urea. Our findings support the emerging urea–cyanoHAB link and the potential importance of urea in freshwater eutrophication. As society becomes increasingly dependent on urea for agricultural crops, the need to understand how urea influences phytoplankton community composition may be instrumental in predicting bloom dynamics.